Técnicas para la enseñanza de matemática - Ayala Martínez, Cindy Gissella (2016)
Education is in a constant process of modernization is a priority for this reason seek alternative implementing change and transformation technology, new strategies and the unavoidable use of techniques for teaching mathematics; this research is considered important to incorporate a training workshop for teachers. The contents of this proposal cover different techniques to optimize resources and make the kind of mathematics more attractive and interesting to the student this factor will allow the development of skills and achievement of established powers. The aim is to raise educational for improving student learning the fifth year of basic education Educational Unit "Genesis" alternative. in the area of mathematics by applying appropriate by teachers in order to improve educational level teaching techniques; the theoretical foundations of the research are based on heuristic method that has a creative and comprehensive vision of education considering the child as a whole, beyond the cognitive aspect to form a whole being still a descriptive research; bibliographic record design and observation, the survey conducted was aimed at teachers, parents and students whose results were tabulated properly .; analysis of the results showed the lack of use of techniques for teaching mathematics in the educational process of students. The impact was obtained with the implementation of the proposal is to strengthen the skills of training on the subject of techniques for teaching mathematics where direct beneficiaries are the entire educational community, teachers who improve their skills in development also use of teaching the student who learn to discover and strengthen their skills and the general community of abilities.